2009
DOI: 10.1111/j.1460-9592.2009.03096.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of anesthesiologic complications in pediatric neurosurgery

Abstract: The duration of anesthesia, the sitting position of the patient, and the presence of comorbidities significantly increase the risk of anesthesia complications in pediatric neurosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
(19 reference statements)
1
20
0
3
Order By: Relevance
“…10,25 To our knowledge, there are only 2 reports of complications in pediatric neurosurgery, only one of which (our previous study 1,2 ) mentions intraoperative complications separately.…”
Section: Neurosurgical Iocsmentioning
confidence: 99%
See 3 more Smart Citations
“…10,25 To our knowledge, there are only 2 reports of complications in pediatric neurosurgery, only one of which (our previous study 1,2 ) mentions intraoperative complications separately.…”
Section: Neurosurgical Iocsmentioning
confidence: 99%
“…In the pediatric anesthesiological literature, the rate of anesthesiological complications is 2.8%-9.6%. 2,12,23 Tay et al reported a 3.4% IOC rate in their neurosurgical subgroup, whereas the IOC rate was 2.8% for all pediatric anesthesiological procedures. It is possible that what we counted as a neurosurgical complication was counted as an anesthesiological complication in that study (especially hemodynamic complications with a surgical cause).…”
Section: Anesthesiological Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies [4,5,6] have reported rates for complications related to anesthesia and surgical procedures of 5.5–40%; the most frequent complications are cerebrospinal fluid leaks, new neurological deficits, obstruction and infection of ventriculoperitoneal shunts, significant bleeding and bradyarrhythmia during the initiation of anesthesia. These studies listed the major complications according to the type of surgery; however, the magnitude of their impact on the progress of the patients remains unknown.…”
Section: Introductionmentioning
confidence: 99%